2015
DOI: 10.1021/acs.molpharmaceut.5b00731
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the pH and Temperature in the Rabbit, Pig, and Monkey Eye: Key Parameters for the Development of Long-Acting Delivery Ocular Strategies

Abstract: Many long-acting delivery strategies for ocular indications rely on pH- and/or temperature-driven release of the therapeutic agent and degradation of the drug carrier. Yet, these physiological parameters are poorly characterized in ocular animal models. These strategies aim at reducing the frequency of dosing, which is of particular interest for the treatment of chronic disorders affecting the posterior segment of the eye, such as macular degeneration that warrants monthly or every other month intravitreal inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 13 publications
1
25
0
2
Order By: Relevance
“…A circulatory motion of AH in the anterior chamber was generated with temperature gradient, heat transfer, and gravity based on the model by Karampatzakis and Samaras (38). The temperature of sclera, choroid, retina and aqueous humor inlet was set 37 o C, and that of cornea to 34 o C (29,39,40).…”
Section: Enhanced Mixing In the Anterior Chamber With Heat Transfermentioning
confidence: 99%
“…A circulatory motion of AH in the anterior chamber was generated with temperature gradient, heat transfer, and gravity based on the model by Karampatzakis and Samaras (38). The temperature of sclera, choroid, retina and aqueous humor inlet was set 37 o C, and that of cornea to 34 o C (29,39,40).…”
Section: Enhanced Mixing In the Anterior Chamber With Heat Transfermentioning
confidence: 99%
“…Humans and pigs share similar anatomic and physiologic characteristics that make pigs useful as experimental models in biomedical research [18,19]. Several studies have reported the characteristics of pig eyes, including parameters of the whole eyeball [20,21], retina [22,23], cornea [24], limbus [25], and the lacrimal gland [26]. However as far as we know, a thorough description of the conjunctiva of the pig eye has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Hal ini juga terjadi pada pH vitreous humor kelinci menjadi 6,83 setelah 30 menit dan 6,54 setelah 90 menit. Nilai pH vitreous humor kera yang disimpan pada suhu 4˚C, meningkat pada (Lorget et al 2015). Nilai pH pada vitreous humor dapat dipengaruhi oleh waktu dan suhu penyimpanan.…”
Section: Derajat Keasamanunclassified
“…Nilai pH pada vitreous humor dapat dipengaruhi oleh waktu dan suhu penyimpanan. Nilai pH pada vitreous humor mata ikan tuna lebih rendah dari pH vitreous humor kelinci dan kera diduga karena meningkatnya produksi asam laktat pada vitreous humor mata ikan tuna (Lorget et al 2015). Vitreous humor mengandung glukosa 5 hingga 10% yang berikatan dengan protein (glikoprotein) dengan total glikoprotein dalam tubuh 20% dari jumlah protein nonkolagenous pada vitreous humor (Sebag 1989).…”
Section: Derajat Keasamanunclassified